2016
DOI: 10.3144/expresspolymlett.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

Solvent free synthesis and structural evaluation of polyurethane films based on poly(ethylene glycol) and poly(caprolactone)

Abstract: Abstract. Biodegradable amphiphilic polyurethane films (bio-PUs) were synthesized by solvent free polyaddition reaction of hydrophilic poly(ethylene glycol) (PEG) and hydrophobic poly(caprolactone) (PCL) as macrodiols with hexamethylene diisocyanate. Samples were subsequently heat cured in order to obtain 3D crosslinked structure. Different PCL/PEG ratios allowed controlling the toughness of the resulting bio-PUs. Significant enhancement of Young's modulus, strength and elongation at break was observed at a PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…2). A catalyst concentration of 0.03 mol.% was chosen according to our previously reported preparation procedure [47]. However, the reaction proceeded much faster in the mixtures with nanofiller than in the neat material, which resulted in nonhomogeneous dispersion of HDI.…”
Section: Nanocomposite Processingmentioning
confidence: 99%
“…2). A catalyst concentration of 0.03 mol.% was chosen according to our previously reported preparation procedure [47]. However, the reaction proceeded much faster in the mixtures with nanofiller than in the neat material, which resulted in nonhomogeneous dispersion of HDI.…”
Section: Nanocomposite Processingmentioning
confidence: 99%
“…46 In the literature, it was reported that incorporation of polycaprolactone (PCL) to the soft segment of the PU films synthesized with HDI and PEG increased the elastic modulus from 3.6 ± 0.2 MPa to 67.8 ± 3.0 MPa. 47 According to the study by Malkappa and Jana, PU films were prepared with hydroxyl terminated polybutadiene (HTPB) and 2,6-TDI. The elastic modulus of the PU film was found to be 0.046 MPa, a value significantly lower than that of our study (1.89 ± 0.09 MPa).…”
Section: Resultsmentioning
confidence: 99%
“…In the first step, HMDI was reacted with PEG to form urethane linkages (-NH-C=O) which can be observed via the appearance of new peaks in the range of 1600-1800 cm −1 , and 1520-1570 cm −1 which represent the carbonyl stretching vibration of amide I, and the link between -NH bending and -C-N stretching vibrations of secondary amide, respectively [30]. The peak at about 1100 cm −1 in the HMDI-PEG mixture (figure 4(a)) was associated to ether (C-O-C) stretching vibration while the peak at about 2880 cm −1 was due to the aliphatic -CH stretching in the PEG chain [31,32]. The remaining free isocyanate (-NCO) that appeared at 2260 cm −1 and the isocyanate terminated HMDI-PEG mixture were then reacted with -OH groups in PCL as PCL was added to the reaction, hence reduced the free NCO peak intensity ( figure 4(b)).…”
Section: Ftir Analysismentioning
confidence: 99%
“…The band IV (at about 1630 cm −1 ) has raised interest because it represents the H-CO groups of the crystalline SS [37,41]. The sharper and obvious H-CO (band IV) of PU-PEG is observed at lower frequency compared to PU-PCL, suggesting higher amount of H-CO groups, due to the higher crystalline domains of PEG [31,42]. In the crystalline phase, the polymeric chains are aligned in parallel to form lamellae, which encouraged the stronger hydrogen bonding formation [31].…”
Section: Microphase Separation Behavior 321 the Effect Of Long Chamentioning
confidence: 99%